The Representations of Toxic Masculinity on Nate Jacobs in Euphoria (2019) - Ayuretno, Annisa; Kinasih, Putri Rindu (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
Despite some changes in how masculinity is portrayed over time, certain disturbing patterns and characteristics continue. Yet, popular media exposure may be the primary way that children and most adults learn about others as well as absorb and internalize social norms, values, and beliefs that are reflected in the way the media is presented and expressed. One disturbing characteristic that is shown in TV series is toxic masculinity. This study aims to study the representation of toxic masculinity in Nate Jacob in the critically acclaimed series Euphoria (2019). In this research, the writers used the qualitative method to gather an in-depth, detailed, and comprehensive portrayal of toxic masculinity based on the characteristics of toxic masculinity proposed by Kupers. This study showed that Nate Jacobs represents Kupers' characteristics of toxic masculinity: misogyny, homophobia, greed, and violent domination. He performs toxic masculinity to prove to himself, symbolically, that he is not like his father. Nate exhibits dominance and violence because of his biggest fear of becoming like his homosexual father